Step-Index Plastic Optical Fibre (SI-POF) Channel Optimisation: M-PAM and Equalization (FULafia Journal of Science and Technology, 2020)
Step-Index Plastic Optical Fibre (SI-POF) is gaining popularity in local area network installations due to its characteristics as an inexpensive medium. This research optimized SI-POF channel of two distances (30metres and 60metres) by introduction of equalizer(s) at the output channel signal with M-PAM (PAM-2 and PAM-4) modulation scheme to address bandwidth limitation and inter symbol interference (ISI). The study which was carried out in MATLAB R2019a environment, study employed decision feedback equalizer-DFE (2, 1), (4, 2) and linear equalizer-LE (2, 0) algorithms to train the output channel signal. The study adopted scatter plots, bit error rate (BER) and data rate (DR) as indices to improve the performance of the output signal.
Keywords: M-PAM; Equalizer; Scatter; BER and DR